Predicting retail banking consumer behaviour using statistics - Agaliotis, Konstantinos; Hadžić, Miroljub (The European Journal of Applied Economics, 2015)
The рurрοѕe οf any eсοnοmiс-based aсtivitу is the creation of needs. As the financial activities are not an exception to this rule, understanding clients’ necessities and their satisfaction is of primary concern for all financial institutions. Being conversant with the exact details that constitute client behaviour and the processes that lead to particular decisions, has become an advantage for financial institutions investing resources in it. Finally, it will not only pay off by satisfying the clients’ needs, but it will also secure a long-standing loyalty and relationships with them. As all relationships, the one between the client and the bank requires support and mutual understanding. Given the Serbian retail banking market, we may conclude the following: firstly, there is still potential for doing business in this filed; secondly, the particular segments of customers would accept new products; and thirdly, banks have to focus on the highest ranking clients concerning their credit worthiness. As regards the client behaviour over different product offerings, we can conclude that cash loans and credit card holders are not price sensitive, and that subsequently, the existing holders intend to increase their credit exposure.